Senseless [large type] - Burton, Mary (Mary T.) (Thorndike Press, 2011)
The vicious burns scarring the victims' flesh reveal the agony of their last moments. Each woman was branded with a star, then stabbed through the heart. With every death, a vengeful killer finds a brief, blissful moment of calm. Soon it's time for the bloodshed to start again. Ten years ago, the end-of-school-year celebration of Eva Rayburn and her sorority sisters turned into a nightmare. She's trying to start over, but a new nightmare has begun.